2019
DOI: 10.1108/cms-04-2018-0489
|View full text |Cite
|
Sign up to set email alerts
|

Leader creativity expectations and follower radical creativity

Abstract: Purpose The purpose of this study is to research the effect of leader creativity expectations on follower radical creativity. Highlighting the implications of leader creativity expectations, the authors examined employee creative process engagement as a mediator and follower perceived procedural justice as a moderator in the relationship between leader creativity expectations and employee radical creativity. Design/methodology/approach A sample of 256 dyads comprising full-time employees and their immediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 73 publications
0
32
1
Order By: Relevance
“…Studies have suggested that power distance has been considered as one of the key factors that facilitate innovation and management in countries with collectivism and high-power distance like China (Xu and Wang, 2019). Farh et al (2007) theorize that power distance plays a negative moderating role in the positive relationship between organizational support and job performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have suggested that power distance has been considered as one of the key factors that facilitate innovation and management in countries with collectivism and high-power distance like China (Xu and Wang, 2019). Farh et al (2007) theorize that power distance plays a negative moderating role in the positive relationship between organizational support and job performance.…”
Section: Introductionmentioning
confidence: 99%
“…Xu and Wang (2019) recently suggested that due to high power distance and a cultural background emphasizing collectivism in China, employees normally spend a lot of efforts in understanding what their leaders expect and take corresponding actions to fulfill the expectations. However, very few studies directly address the relationship between power distance and Chinese new venture performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…158 orientation can affect a person's creative power fostering. In prior, it has been shown that leader-member exchange, creative role identity, leader creativity expectation, leader-followers creativity expectation, and creative process engagement can influence the creativity of employees (Lin, Ma, Zhang, Li, & Jiang, 2018;An-chih Wang & Cheng, 2009) (Qu, Janssen, & Shi, 2017;Xu & Wang, 2019).but the scholars and researchers rarely emphasized on the interactive effects of benevolent leadership and voice behavior considering the power distance differentiation. There is seldom looked up the benevolent leadership and radical creativity.…”
Section: Ijrbs Vol 10 No 3 Issn: 2147-4478mentioning
confidence: 99%
“…In the meantime, we managed and controlled gender, age, education, role, and organizational tenure of employees while testing hypotheses, given their possible effect on voice(Y. Li & Sun, 2015a) and creativity (Xu & Wang, 2019). In the light of previous research (Dedahanov, Lee, Rhee, & Yoon, 2016b), when controlling for age, occupation, positions, and tenure in the organization, which has a significant impact on creativity.…”
Section: Followers Radical Creativitymentioning
confidence: 99%